2015
DOI: 10.1001/jamapsychiatry.2015.0082
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Depression and Diabetes Mellitus on the Risk for Dementia

Abstract: IMPORTANCE Although depression and type 2 diabetes mellitus (DM) may independently increase the risk for dementia, no studies have examined whether the risk for dementia among people with comorbid depression and DM is higher than the sum of each exposure individually.OBJECTIVE To examine the risk for all-cause dementia among persons with depression, DM, or both compared with persons with neither exposure. DESIGN, SETTING, AND PARTICIPANTSWe performed a national population-based cohort study of 2 454 532 adults… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
111
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(124 citation statements)
references
References 45 publications
7
111
1
5
Order By: Relevance
“…Our findings are in line with previous studies on the higher prevalence of psychiatric morbidity in AD patients (4,5) and studies that investigated depression (7,8,39) as a risk factor for AD. Previous studies with narrow or non-existent time window between depression and AD/dementia reported an association between depression and AD/dementia (5,22,23) while studies with wider time window yielded inconsistent results (5,8,10,40).…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are in line with previous studies on the higher prevalence of psychiatric morbidity in AD patients (4,5) and studies that investigated depression (7,8,39) as a risk factor for AD. Previous studies with narrow or non-existent time window between depression and AD/dementia reported an association between depression and AD/dementia (5,22,23) while studies with wider time window yielded inconsistent results (5,8,10,40).…”
Section: Discussionsupporting
confidence: 93%
“…Between 2011 and 2012, 130,000 people or 4.97% of those aged 65 years and over in Taiwan had dementia [2]. Diseases including diabetes mellitus [3,4,5], hypertension [6,7], hyperlipidemia [8], obesity [9,10], depression [11,12], traumatic brain injury [13,14], stroke [15,16], and chronic kidney disease [17,18] have been associated with an increased risk of dementia in previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…In turn, this could help prevent long-term complications of these conditions, such as type 2 diabetes mellitus, cardiovascular disease, and dementia. 3,15,17,98 If successful, this study will offer the potential to change how obese and depressed adults are treated using an integrated multicondition collaborative care model in primary care.…”
Section: Discussionmentioning
confidence: 99%